Prudent use and antimicrobial prescription practices in Ethiopian veterinary clinics located in different agroecological areas - Tufa, T.B.; Amenu, Kebede; Fasil, N.; Regassa, F.; Beyene, T.J.; Revie, C.W.; Hogeveen, H.; Stegeman, J.A. (Springer, 2024)
Background: Understanding antimicrobial prescribing (AMP) practices and their prudent use in livestock can support the implementation of stewardship programs in veterinary medicine. Empiric therapy using antimicrobials is widely practiced in resource-poor settings, including Ethiopia. This could significantly contribute to the global burden of antimicrobial resistance (AMR) and the potential accumulation of residues in food. This study assessed AMP practices in Ethiopian veterinary clinics located in different agroecological zones (AEZs) as well as adherence to antimicrobial stewardship principles (ASPs).